The role of intellectual capital in promoting financial performance an applied study on a sample of the companies listed in Iraq stock exchange - كاظم فائق جواد (Journal of Economics and Administrative Sciences, 2014)
The interest in the intellectual capital and its development is a civilized necessity imposed by the requirements of the times and cannot imagine an advanced society in its potential productivity in poor efficiency of human capital, and features the work environment change permanently, putting the management of financial companies against a constant challenge toward coping with new developments in this changing environment and this is not taken unless owned by these companies qualified human resources and the provision of Culture organizers have, which manifested itself with the research problem by the following two questions: Did the intellectual capital value specific financial and quantifiable data on the use of the financial situation of the companies and their financial markets environment? Did the value of intellectual capital in the event of corporate profitability measured explain variation as one in which the dimensions of the financial performance are materialized? The aim of the research into the possibility of measuring intellectual capital quantitative research into the possibility of measuring intellectual capital using quantitative measurements of financial sense to try the financial evaluation of the intangible assets of the knowledge of the companies studied sample. Experimental Investigation of the relationship between the value of the intellectual capital and the profitability of a number of Iraqi companies listed and traded in the Iraqi market for securities and to investigate the nature of that relationship, the direction, and the significance. The research sample has consisted of (30) of the total company Iraqi companies listed and traded in the Iraqi, which are (73) companies in 2012. The most prominent results are the validity of the model test in the interpretation of the relationship between the value of intellectual capital and financial performance of the companies studied focusing on profitability, and forecast the trends expected future after he demonstrated regression results of statistically significant between the variables studied in the light of repeat testing process because of the multiplicity of measurements of profitability through the use of standard return on assets and return on the right of ownership, and then the direction as supplemented strongly exponential relationship between the two variables studied. With regard to the recommendations of the research, it has emerged; including the need to investigate the question of whether it was possible to conduct prospective studies focused on the study of each component of intellectual capital, individually and collectively, with its effect on the financial performance and then find out the most influential component in it.